Development of Online Mechanics Concept Inventory (OMCI) Instrument Based on Local Wisdom - Pujiyanti, Arik; Mindyarto, Budi Naini; Astuti, Budi (Universitas Negeri Semarang, 2023)
This study discusses the development of online mechanics concept inventory (OMCI) instrument based on local wisdom. The purpose of this study to determine the quality of the online mechanics concept inventory instrument based on local wisdom. The type of this research is Research and Development (RD). The developed instrument is integrated with local wisdom, so that every item has literacy as a stimulus for the question. The concept inventory instrument is one of the test tools presented online which is used to measure students' conceptual understanding. The research model used is Borg and Gall. The instrument developed were validated by expert judgment. The results of the validation assessment are in the form of qualitative and quantitative content validity. The results of qualitative validity can be seen in terms of materials obtained on an average of 99.2%, construction is averaged 93.3%, and language is averaged 97.4%. While the quantitative analysis of validity is done using Aiken's v equations obtained an average of 0.841 of valored 0.841 is so high, it is worth being used to measure understanding the conception of learners.